Children and young people's decision-making in social research about sensitive issues. Issue 6 (2nd November 2021) - Moore, Tim; McArthur, Morag; Graham, Anne; Chalmers, Jenny; Powell, Mary Ann; Taplin, Stephanie
ABSTRACT: Limited attention has been given to what motivates and informs children and young people's decision to participate (or not) in social research, especially about sensitive issues. This paper reports the findings from focus group interviews with children and young people aged 9–16 years, undertaken as part of a larger study that explored what constitutes a sensitive issue in social research and the factors considered when deciding to participate. Participants articulated a range of intrinsic and extrinsic motivations: benefiting others, getting something out of it, getting things 'off your chest' and the role of incentives and trusted adults. While similar to findings about medical research, the data from this study provides deeper insight into how children and young people make decisions to participate in social research. The critical role that accessible information plays in supporting children's considered decision-making is highlighted, along with rich insights into why research might matter for themselves and others.